Implementation of records management system in corporate environment. - Siew, Peck Shiong. (2008)
Records are natural by-products of the activities of an organisation. They are unique resources that bring about an enormous responsibility. They contribute to the efficiency and effectiveness of the business functions. They are the carriers of the lifeblood of the organisation: its own information, past, present and future. Therefore, the importance of records management cannot and should not be underestimated. The research paper captured the process of implementing a records management system in a corporation environment, a Statutory Board. The limitation of the old registry system capability, complicated & unsystematic file classification have brought about several operational issues. From users' perspective, they did not have an adequate understanding of the role & function of Registry and their role being the users. Hence, the sense of responsibility by the individual document contributor is less satisfactory.